Digital Literacy Learning Module Improves Knowledge of Healthy Food in Indonesian PAUD Students - Siti Aisyah; Dian Novita; Trini Prastati; Titi Chandrawati; Anita Chandra Dewi Sagala (Universitas Pendidikan Ganesha, 2023)
Children are active in online activities, especially on social media. It leads to an urgent need to increase digital literacy early to minimize the risks of online harm. This study analyzes the effectiveness of digital literacy modules and learning media in the COVID-19 pandemic by using digital learning resources such as videos and electronic books. This type of research is quantitative. The method used is a descriptive method with a quantitative approach. The sample in this study was 219 people, namely early childhood 5-6 years, teachers, and parents. The data collection technique for this research used a pre-test and post-test and a questionnaire with a Likert scale. The data analysis technique used is paired t-test. The study results demonstrate the relevance and applicability of e-learning modules in content and structure for children, particularly in developing awareness about healthy eating. It was concluded that digital literacy learning modules and media were quite effective and made it easier for students to absorb learning material from teachers with diverse backgrounds and abilities.